Between History and Memory: A Source Contribution to the Historiographical Tradition of the Teutonic Knights c. 1500, Part I. - Leighton, Gregory J. (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
The present article is the first of two pieces concerning historiography and memory within the Prussian Branch of the Teutonic Order c. 1500. Its subject is an unpublished text written in Prussia around 1500 and kept in the archives of the Teutonic Order in Berlin (Berlin, GStA PK, XX. HA, OBA, no. 29077). It will provide some possible explanations for the background of the source, its contents, in addition to noting the most interesting elements in its recounting of the conquest of Prussia. While the text under study largely conforms to the traditional representations of the conquest of Prussia in the Teutonic Order’s chronicles, there are digressions and changes which deserve attention. As such, the article presents a new source for future research on the historiographical tradition of the Teutonic Order and the ways in which it was changing on the eve of the secularization of Prussia in 1525.